Structure and activity of lacustrine sediment bacteria involved in nutrient and iron cycles - Martins, Gilberto (2011)
Knowledge about the bacterial community structure in sediments is essential to better design restoration strategies for eutrophied lakes. In that regard, the aim of this study was to quantify the abundance and activity of bacteria involved in nutrient and iron cycling in sediments from four Azorean lakes with distinct trophic states (Verde, Azul, Furnas and Fogo). Inferred from quantitative PCR, bacteria performing anaerobic ammonia oxidation, were the most abundant in the eutrophic lakes Verde, Azul and Furnas (4.5 % to 16.6 %), followed by nitrifying bacteria (0.8 % to 13.0 %), denitrifying bacteria (0.5 % to 6.8 %), iron-reducing bacteria (0.2 % to 1.4 %), and phosphorus-accumulating organisms (<0.3 %). In contrast, denitrifying bacteria dominated sediments from the oligo-mesotrophic lake Fogo (8.8 %). Activity assays suggested that bacteria performing ammonia oxidation (aerobic and anaerobic), nitrite oxidation, heterothrophic nitrate reduction, iron reduction and biological phosphorus storage/release were present and active in all Azorean lake sediments. The present work also suggested that the activity of denitrifying bacteria might contribute to the release of phosphorus from sediments.